Small business, big vision : lessons on how to dominate your market from self-made entreprenuers who did it right - Toren, Adam, 1975-; Toren, Matthew (Hoboken, N.J. : Wiley, 2011)
'The world of today's entrepreneur is far different from the business climates of past generations.As quickly as technology and the economy are changing, and as impactful as those changes are on our society, the ability to embrace and effectively integrate change has become more vital than being experienced. Regardless of one's age in years, a young mindset is what it takes to thrive as an entrepreneur today. 'The way we've always done it,' isn't relevant in today's business world.The profiles in Small Business, Big Vision portray entrepreneurs who demonstrate that'flexible' and'adaptable' are the new'dependable' and'steadfast.' The 7 Steps for entrepreneur success are: Toss Your Business Plan Out the Window Investors- Out! Collaborators- In! The Toothless MBA Hiring Employees [is] for Dummies Laser-Sighted Marketing Pulling a 180 It's Not all About You'--
Keywords: Small business -- Management; Entrepreneurship; Success in business; BUSINESS & ECONOMICS / Entrepreneurship